New Delhi metallo-β-lactamase-1 (NDM-1) Escherichia coli isolated from household vacuum cleaner—Oregon, 2013. (2017) - Buser, Genevieve L.; Cassidy, P. Maureen; Pfeiffer, Christopher D.; Townes, John M.; Morey, Karim E.; Rayar, Jaipreet; Kutumbaka, Kirthi K.; Han, Sukkyun; Nadala, Cesar; Samadpour, Mansour; Weissman, Scott J.; Vega, Robert; et al.
Abstract: The first Oregon case of New Delhi metallo-β-lactamase-1 (NDM-1)-producing Escherichia coli was reported during November 2013. Epidemiologic investigation revealed only local outpatient medical care and no travel outside Oregon for both the patient and his household contact. Environmental sampling discovered a matching isolate from the patient's household vacuum cleaner, suggesting environmental persistence.